Protein Bodies in Leaves Exchange Contents through the Endoplasmic Reticulum - Saberianfar, Reza; Sattarzadeh, Amirali; Joensuu, Jussi J.; Kohalmi, Susanne E.; Menassa, Rima (Frontiers in Plant Science, 2016)
Protein bodies (PBs) are organelles found in seeds whose main function is the storage of proteins that are used during germination for sustaining growth. PBs can also be induced to form in leaves when foreign proteins are produced at high levels in the endoplasmic reticulum (ER) and when fused to one of three tags: Zera®, elastin-like polypeptides (ELP), or hydrophobin-I (HFBI). In this study, we investigate the differences between ELP, HFBI and Zera PB formation, packing, and communication. Our results confirm the ER origin of all three fusion-tag-induced PBs. We show that secretory pathway proteins can be sequestered into all types of PBs but with different patterns, and that different fusion tags can target a specific protein to different PBs. Zera PBs are mobile and dependent on actomyosin motility similar to ELP and HFBI PBs. We show in vivo trafficking of proteins between PBs using GFP photoconversion. We also show that protein trafficking between ELP or HFBI PBs is faster and proteins travel further when compared to Zera PBs. Our results indicate that fusion-tag-induced PBs do not represent terminally stored cytosolic organelles, but that they form in, and remain part of the ER, and dynamically communicate with each other via the ER. We hypothesize that the previously documented PB mobility along the actin cytoskeleton is associated with ER movement rather than independent streaming of detached organelles.